2013
DOI: 10.1073/pnas.1218509110
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin homologue from H17N10 bat influenza virus exhibits divergent receptor-binding and pH-dependent fusion activities

Abstract: Bat influenza virus H17N10 represents a distinct lineage of influenza A viruses with gene segments coding for proteins that are homologs of the surface antigens, hemagglutinin (HA) and neuraminidase (NA). Our recent study of the N10 NA homolog revealed an NA-like structure, but with a highly divergent putative active site exhibiting little or no NA activity, and provided strong motivation for performing equivalent structural and functional analyses of the H17 HA protein. The overall structure of the H17 HA hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 30 publications
5
113
0
1
Order By: Relevance
“…Considering the interaction between HA and NA and their importance for infecting cells, several attempts to rescue a reassortant with HA and NA from PR8 and the other six gene segments from H17N10 were unsuccessful, which is consistent with the results from previous studies (Juozapaitis et al, 2014;Zhou et al, 2014). We did not perform these experiments with HA and NA from H17N10 and the other six segments from PR8, considering that the receptors for H17N10 HA and NA are still unknown and that HA was unable to bind any known cell line Sun et al, 2013;Zhu et al, 2012Zhu et al, , 2013. The combination of PB2, PB1, PA and NP from H17N10 together with the other four segments from PR8 did not result in the production of replicative influenza viruses either, even though polymerase activity of the ribonuclear protein (RNP) complex was confirmed in human cells with minigenome reporter assay (Tong et al, 2012, Juozapaitis et al, 2014, which was reproduced in our study (data not shown).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Considering the interaction between HA and NA and their importance for infecting cells, several attempts to rescue a reassortant with HA and NA from PR8 and the other six gene segments from H17N10 were unsuccessful, which is consistent with the results from previous studies (Juozapaitis et al, 2014;Zhou et al, 2014). We did not perform these experiments with HA and NA from H17N10 and the other six segments from PR8, considering that the receptors for H17N10 HA and NA are still unknown and that HA was unable to bind any known cell line Sun et al, 2013;Zhu et al, 2012Zhu et al, , 2013. The combination of PB2, PB1, PA and NP from H17N10 together with the other four segments from PR8 did not result in the production of replicative influenza viruses either, even though polymerase activity of the ribonuclear protein (RNP) complex was confirmed in human cells with minigenome reporter assay (Tong et al, 2012, Juozapaitis et al, 2014, which was reproduced in our study (data not shown).…”
Section: Resultssupporting
confidence: 84%
“…Previous research has demonstrated that the bat-derived neuraminidase-like N10/N11 and haemagglutinin H17/H18 have different functions compared to their homologues in other influenza viruses . N10 and N11 lack sialidase activity on tested sialic-acidcontaining oligosaccharides Tong et al, 2013;Zhu et al, 2012), and the H17 and H18 proteins did not bind to the canonical sialic acid receptors Tong et al, 2013;Zhu et al, 2013). These results suggest that H17N10 and H18N11 are influenza-like viruses that are related to categorized influenza A viruses but seem incompatible in function and reassortment capability.…”
Section: Introductionmentioning
confidence: 89%
“…The surface glycoprotein hemagglutinin (HA) is responsible for virus entry and fusion by binding to the cellular receptor, sialic acid (SA) (Rogers et al, 1983). There are 16 serotypes of HA to date with a newly identifi ed H17 from bat whose function is distinct (Tong et al, 2012;Sun et al, 2013;Zhu et al, 2013). HA is one of the major genetic traits for interspecies transmission (Neumann et al, 2009).…”
Section: Structural Basis For Receptor-binding Changesmentioning
confidence: 99%
“…These fusion inhibitors can be subdivided into inhibitors of the group 1 HAs and inhibitors of the group 2 HAs (13). Fusion inhibitors targeting group 1 HAs include CL-61917, CL-385319, and CL-62554 (15), Stachyflin (16), BMY-27709 (17), LY-180299 (18), RO5464466 and RO5487624 (19), and N-(1-thia-4-azaspiro [4.5]decan-4-yl) carboxamide inhibitors (19), while TBHQ (20,21) and S19 and C22 (22) are the currently known fusion inhibitors for group 2 HAs. Recently, arbidol (23) was proposed to be a fusion inhibitor of both group 1 and group 2 HAs.…”
Section: Here We Report Two Structurally Distinctive Novel Fusion Inhmentioning
confidence: 99%